SOSIALISASI PEMANENAN DAN PEMANFAATAN AIR HUJAN DI DESA REJOSARI KABUPATEN MADIUN - Seno Aji; Hery Hermawan; Mustafa; M Arif Bakhtiar Efendi (JURNAL DAYA-MAS, 2025)
This society's service activity aimed to raise public awareness about preserving the surrounding environment. This was because in Madiun Regency there are several areas that experience floods and droughts. Some of these areas experience flooding during the rainy season. However, in the dry season, the region experiences drought. Based on this, this socialization activity was carried out. The society service method used was the socialization of rainwater harvesting and utilization as an alternative to clean water. The results showed that the community gained knowledge about rainwater and developed awareness to participate in preserving the surrounding environment. Another result was that the community gained knowledge about how to harvest and utilize rainwater properly and effectively.